Pengaruh Lingkungan Kerja, Disiplin Kerja, dan Komunikasi Terhadap Kepuasan Kerja Karyawan Bankaltimtara Unit Usaha Syariah KC Balikpapan - Faradina Ayu Indria Anggraeni; Didik Hadiyatno; Rahajeng Cahyaning Putri Cipto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this research is to determine the influence of the work environment, work discipline and communication on the job satisfaction of employees of Bankaltimtara Unit Usaha Syariah KC Balikpapan. The type of research used is quantitative research. The sampling technique in this research was purposive sampling with a sample size of 55 employees of Bankaltimtara Sharia Business Unit KC Balikpapan. The data collection method was carried out by distributing questionnaires. This research uses SmartPLS to process data. The data analysis method in this research uses outer models, inner models, basic equations and booststrapping tests. The results of this research show that work environment variables have a positive and significant effect on the job satisfaction of employees of Bankaltimtara Unit Usaha Syariah KC Balikpapan. The work discipline variable has a positive and significant influence on the job satisfaction of employees of Bankaltimtara Sharia Business Unit KC Balikpapan. And the communication variable has a positive and significant effect on employee satisfaction at Bankaltimtara Unit Usaha Syariah KC Balikpapan.